Optical properties of hydrothermally synthesised and thermally annealed ZnO/ZnO2 composites - Rodrigues, Joana (2021)
ZnO/ZnO2 composites grown by hydrothermal synthesis at low temperature (180 °C) and thermally annealed at 300 °C were fully analysed by morphological, structural and optical techniques. X-ray diffraction patterns (XRD) and Raman spectroscopy clearly evidence the presence of both crystalline phases in the ZnO/ZnO2 sample. The differential scanning calorimetry analysis and thermogravimetric profiles indicate an exothermic event with a peak temperature ca. 225 °C, which is accompanied by a 8.5% weight loss, being attributed to the crystallization of ZnO from ZnO2. Upon a thermal annealing treatment at 300 °C the ZnO2 phase was completely converted into ZnO, as measured by XRD and Raman spectroscopy. Photoluminescence investigations reveal that the emission is dominated by a broad band recombination in both samples, due to the overlapping of different emitting centres, and that the peak position of the PL emission is dependent on the excitation density. The ZnO/ZnO2 sample exhibits a widening of the bandgap when compared to the one only containing ZnO, likely related to the presence of the additional ZnO2 phase and suggesting a bandgap energy of ~3.42 eV for this compound. Surface analysis revealed that the sample exhibits a surface area of 90 m2 g−1, which decreases to 30 m2 g−1 after the thermal annealing and the full conversion into ZnO. This difference in the surface area showed particular relevance in the stability of the measured optical properties. Particularly, the intensity of the photoluminescence signal was seen to be higher in the ZnO/ZnO2 sample and strongly dependent on the measurement atmosphere, highlighting its potential to be employed in the fabrication of optical-based sensing systems for environmental applications, namely in gas sensors.